REDUCTION OF TUMOR NECROSIS FACTOR-ALPHA AND INTERFERON-GAMMA CONCENTRATION ON TUBERCULOSIS WITH DIABETES MELLITUS AS A MARKER IN DECREASE IMMUNE SYSTEM - NELLY MARISSA; NUR RAMADHAN; SARI HANUM; MARLINDA; EKA FITRIA; ABIDAH NUR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study aimed to determine the decreased immune response of tuberculosis (TB) with diabetes mellitus (DM) patients. Methods: A total of 105 TB patients who were undergoing treatment at health centers and hospitals in Banda Aceh and Aceh Besar were included in this study. Data collection was carried out by interviewed to obtained demographic and respondent categories based on the diagnosis. Measurements of height and weight were also conducted to obtain body mass index data. 5 mL peripheral blood was taken from each respondent group into a TB with DM (TB+DM) and TB without DM (TB-DM). The blood tested usage tumor necrosis factor-alpha (TNF-α) level using enzyme-linked immunosorbent assay and interferon-gamma (IFN-γ) using IFN-γ release assay. Results: The average concentration of both TNF-α and IFN-γ was higher in TB-DM group (TNF-a 5.2 pg/mL; IFN-g 1.5 IU/mL) than in TB+DM group (TNF-a 2.06 pg/mL; IFN-g 2.86 IU/mL). There were significant differences in TNF-α between the two groups but no significant differences in IFN-γ protein concentration. Conclusion: The immune response of TB patients with DM symptoms was markedly reduced by the decreased expression of TNF-α and IFN-γ.